Role of carbon defects in the reversible alloying states of red phosphorus composite anodes for efficient sodium ion batteries. Issue 11 (2nd March 2017) - Li, Mengya; Carter, Rachel; Oakes, Landon; Douglas, Anna; Muralidharan, Nitin; Pint, Cary L.
Abstract : Here we report the first mechanistic study investigating the effect of carbon defects on the evolution of different sodium–red phosphorus (red P) alloy states for stable high capacity sodium ion battery anodes. Abstract : Here we report the first mechanistic study investigating the effect of carbon defects on the evolution of different sodium–red phosphorus (red P) alloy states for stable high capacity sodium ion battery anodes. Using tunable sp 2 /sp 3 carbon composites containing controlled single-walled carbon nanotube (SWCNT) and single-walled carbon nanohorn (SWCNH) compositions, we identify potentials over which both stable and unstable alloying of red P occurs with sodium. Examination of the stable alloy region includes both NaP and Na5 P4 formation that occurs between 0.40 and 0.15 V where alloying is mostly independent of the carbon composite matrix chemistry. However, an unstable region corresponding to Na3 P formation below 0.15 V results in capacity degradation that directly correlates with the density of carbon defects. In the unstable region, defects are observed to initiate deep alloying and poor reversibility due to the formation of irreversible Na3 P products that form over the carbon surface. Our results present a mechanistic roadmap to guide the design of red P–carbon composite anodes to approach high theoretical sodium ion capacity (2596 mA h g −1 ) while simultaneously addressing chemical interactions that compromise performance stability.